2017
DOI: 10.2967/jnumed.116.184457
|View full text |Cite
|
Sign up to set email alerts
|

Detection Efficacy of Hybrid 68Ga-PSMA Ligand PET/CT in Prostate Cancer Patients with Biochemical Recurrence After Primary Radiation Therapy Defined by Phoenix Criteria

Abstract: The aim of this retrospective study was to evaluate the detection rate of Glu-NH-CO-NH-Lys-(Ahx)-[ 68 Ga(HBED-CC)] ( 68 Ga-PSMA ligand; PSMA is prostate-specific membrane antigen) PET/CT in patients with biochemical recurrent prostate cancer defined by Phoenix criteria after external-beam radiotherapy or brachytherapy as primary treatment. Methods: One hundred eighteen patients with a median prostate-specific antigen (PSA) of 6.4 ng/mL (range, 2.2-158.4 ng/mL; interquartile range, 4.2-10.2 ng/mL) were finally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
9
44
0
2
Order By: Relevance
“…The final PSA value identified by Caroli et al [1] for the identification of positive 68 Ga-PSMA PET/CT was 1.062 ng/ mL, similar to the cut-off value reported for Choline PET/CT [9,10]. However, as clearly stated by the authors, patients with a PSA value <2 ng/mL and with a GS > 7 and a negative Choline PET/CT would have a positive 68 Ga-PSMA PET/CT in 57 and 81% of cases, although the correlation between PSMA with Gleason score was poor [4,5]. Again, some questions and new data are necessary in order to understand the exact relationship between the aggressiveness of prostate cancer and expression of PSMA.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The final PSA value identified by Caroli et al [1] for the identification of positive 68 Ga-PSMA PET/CT was 1.062 ng/ mL, similar to the cut-off value reported for Choline PET/CT [9,10]. However, as clearly stated by the authors, patients with a PSA value <2 ng/mL and with a GS > 7 and a negative Choline PET/CT would have a positive 68 Ga-PSMA PET/CT in 57 and 81% of cases, although the correlation between PSMA with Gleason score was poor [4,5]. Again, some questions and new data are necessary in order to understand the exact relationship between the aggressiveness of prostate cancer and expression of PSMA.…”
supporting
confidence: 80%
“…Conversely, Giovacchini et al [3] did not find any correlation between 11 C-Choline positivity and Gleason score, at multivariate analysis. Similarly, any correlation between the tumor differentiation and 68 Ga-PSMA has been demonstrated [4,5].…”
mentioning
confidence: 95%
“…Afshar-Oromieh et al used two different protocols: in the first protocol, first two nuclear medicine physicians evaluated the data separately and afterwards together [29], and another protocol where two nuclear medicine physicians together with an assistant radiology physician supervised by a board-certified radiology physician evaluated the image series and a board-certified nuclear medicine physician reevaluated the patients PSMA PET/CT [10]. In two separate studies, authors have evaluated the interreader variability of a nuclear medicine physician and a radiologist and compared the results with consensus finding [9,30]. A detailed description of the differences in reading between the physicians is not documented in the studies cited here.…”
Section: Interobserver Variabilitymentioning
confidence: 99%
“…A variety of closely related compounds are under investigation [29]. Retrospective studies have suggested a high sensitivity of PET using 68 Ga-PSMA ligands in early restaging of prostate cancer but, as with other PET tracers, their value in primary tumour staging is yet to be determined, especially in patients with high-risk disease [30, 31]. Moreover, large prospective studies are required to confirm their imaging performance and clinical impact.…”
Section: Psma and Somatostatin Receptor Imaging And Therapy: High Thrmentioning
confidence: 99%